Transformation of the employees into brand advocates through employer branding - Ilyas, Muhammad Awais; Shaari, Hasnizam; Alshuaibi, Ahmad Said Ibrahim (HMARS, 2018)
In the social media era, the extra ordinary enhancement in communication power of employee aroused the challenge for organizations how to effectively manage the benefits and risks which associated with employees thoughts sharing about their employer with external stakeholders, thus the employee’s communication power about their brand has made employee brand advocacy a buzzword in internal marketing literature. The limitation and restriction for branding is no longer for only products even organizations resorting to branding for attracting and retaining the best talent, now time changed the people more trust on the organization based on the existing employees word of mouth in recruitment which means talent attraction also dependent on employee brand advocacy. Existing literature indicates the clear gap as employee brand advocacy not studied as a pure focal concept. Hence, the present study conceptualised the employer branding relationship with employee brand advocacy.